Role of complex N-glycans in plant stress tolerance - von Schaewen, Antje (Landes Bioscience, 2008)
In plant cells, glycans attached to asparagine (N) residues of proteins undergo various modifications in the endoplasmic reticulum and the Golgi apparatus. The N-glycan modifications in the Golgi apparatus result in complex N-glycans attached to membrane proteins, secreted proteins and vacuolar proteins. Recently, we have investigated the role of complex N-glycans in plants using a series of Arabidopsis thaliana mutants affected in complex N-glycan biosynthesis.1 Several mutant plants including complex glycan 1 (cgl1) displayed a salt-sensitive phenotype during their root growth, which was associated with radial swelling and loss of apical dominance. Among the proteins whose N-glycans are affected by the cgl1 mutation is a membrane anchored β1,4-endoglucanase, KORRIGAN1/RADIALLY SWOLLEN 2 (KOR1/RSW2) involved in cellulose biosynthesis. The cgl1 mutation strongly enhanced the phenotype of a temperature sensitive allele of KOR1/RSW2 (rsw2-1) even at the permissive temperature. This establishes that plant complex N-glycan modification is important for the in vivo function of KOR1/RSW2. Furthermore, rsw2-1 as well as another cellulose biosynthesis mutant rsw1-1 exhibited also a salt-sensitive phenotype at the permissive temperature. Based on these findings, we propose that one of the mechanisms that cause salt-induced root growth arrest is dysfunction of cell wall biosynthesis that induces mitotic arrest in the root apical meristem.